2016
DOI: 10.1074/jbc.m116.744623
|View full text |Cite
|
Sign up to set email alerts
|

Structural Plasticity of Cholesteryl Ester Transfer Protein Assists the Lipid Transfer Activity

Abstract: Coronary heart disease (CHD)2 is one of the prime causes of an increase in the mortality rate worldwide. Over the past few years, various epidemiological studies have provided ample evidence that increased levels of HDL, by transporting cholesterol from atherosclerotic plaques to liver for excretion, can arrest the progression of CHD (1, 2). Subsequent preclinical studies on overexpression of apolipoprotein A-I (apoA-I), the major protein constituent of HDL, have reported significant reduction in CHD risk (3, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(56 citation statements)
references
References 47 publications
5
51
0
Order By: Relevance
“…The subsequent visual inspection of the trajectory demonstrates that the frequent inter-switching of TG C between the chair and trident/random conformations is the possible reason for the variation in CETP tunnel length. The extended tunnel observed in the current study is consistent with our recent report on the structural plasticity of CE-bound CETP, where we have shown that CE-bound CETP frequently switches to an extended conformation of about 100 Å in length 14 . Thus all these analyses suggest that TG-bound CETP maintains a similar stable conformation as that of the CE bound CETP.
Figure 6Comparison of TG- and CE-bound CETP structures.
…”
Section: Resultssupporting
confidence: 93%
“…The subsequent visual inspection of the trajectory demonstrates that the frequent inter-switching of TG C between the chair and trident/random conformations is the possible reason for the variation in CETP tunnel length. The extended tunnel observed in the current study is consistent with our recent report on the structural plasticity of CE-bound CETP, where we have shown that CE-bound CETP frequently switches to an extended conformation of about 100 Å in length 14 . Thus all these analyses suggest that TG-bound CETP maintains a similar stable conformation as that of the CE bound CETP.
Figure 6Comparison of TG- and CE-bound CETP structures.
…”
Section: Resultssupporting
confidence: 93%
“…That study identified the presence of a continuous, central tunnel within the CETP molecule, which is unique among members of the LTP/LBP gene family. Qiu et al further identified two lipid binding pockets in the N-and C-terminal domains of CETP (18,19), and an amphipathic helix, helix X, that is located in the C-terminal domain of the protein. The central CETP tunnel can accommodate two CE molecules, one CE and one TG molecule, or two TG molecules (18).…”
Section: Structure Of Cetpmentioning
confidence: 99%
“…The results of these studies support the penetration of the N-terminal domain of CETP into the surface of an HDL particle together with a concomitant interaction of the C-terminal domain of CETP with an LDL or VLDL particle. Additional analyses have indicated that the transfer of cholesteryl esters between HDLs and LDLs, or HDLs and VLDLs, by this mechanism is dependent on conformational changes in the N-and the C-terminal domains of CETP that increase tunnel continuity and improve neutral lipid accessibility (19,21). …”
Section: Mechanism Of Action Of Cetpmentioning
confidence: 99%
“…More recent electron microscopy (EM) images revealed that the N‐terminal of CETP‐C penetrates the HDL surface and core (∼50 Å), whereas the C‐terminal penetrates the LDL or VLDL only ∼25 Å . Furthermore, molecular dynamics (MD) simulations showed that a hydrophobic tunneling inside CETP‐C is sufficient to allow a CE molecule to completely transfer through the entire CETP . These results strongly suggest a tunneling mechanism, in which the cavities of CETP form a continuous tunneling that mediates the CE‐TG transfer .…”
Section: Introductionmentioning
confidence: 98%
“…While plasma CETP has 4 potential N‐linked glycosylation sites (CETP‐G), which play an important role in the heteroexchange of CEs and TGs between lipoproteins . Up to now, most studies on CETP have only focused on the nascent structure of CETP (CETP‐N, mutated residues were reversed) and CETP‐C . Thus, little is known about the detailed structural information of CETP‐G and effect of glycans on the structure and function of CETP, as well as the accompanying modulation of CEs transfer.…”
Section: Introductionmentioning
confidence: 99%